Characterization of the seed proteins of velvet bean (Mucuna pruriens) from Nigeria - Machuka, J. (Elsevier, 2000)
This paper reports the preliminary characterization of seed protein fractions from seven varieties of velvet beans (Mucuna pruriens) grown in Nigeria, using sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS–PAGE). Three of the most abundant polypeptides, with approximate Mr of 23, 26 and 30 kDa, respectively, were further separated by preparative native-PAGE. N-terminal sequencing revealed the presence of the consensus sequence DDREPV-DT–PL that is also present in the soybean Kunitz-type trypsin inhibitor. The albumin fraction was also shown to contain both trypsin and chymotrypsin inhibitors through enzyme inhibitor assays. Western analysis using antibodies, raised against a representative, 23 kDa polypeptide, indicated that this protein species accumulates exclusively during seed development, suggesting a role in seed storage. Haemagglutination assays using rabbit erythrocytes failed to detect the presence of lectins. The results are discussed within the context of the role of lectins and protease inhibitors in storage and plant defence. The findings are also relevant in view of the toxic and antimetabolic effects of these proteins, which determine the acceptability and adoption of velvet beans as animal and human feed.